DRAINAGE ANALYSIS AND PLANNING IN FLOOD PREVENTION EFFORTS IN GRAND MADANI MOJOKERTO HOUSING - Heru Setiyo Cahyono; Chairumin Alfin; Nur Latifah Khomsiati; Annisa' Carina (Faculty of Engineering, Universitas Islam Darul Ulum Lamongan, 2025)
This study analyzes flood levels for the 2025 re-period in the Grand Madani Housing area, Gunung Gedangan Village, Mojokerto City. The study includes hydrological and hydraulic analysis using 10 years of rainfall data (2014 – 2023) from Mojosari Station, topographic analysis (Sungai Sadar watershed) and soil type (Sub – Sadar watershed), as well as drainage design based on the Rational method, HEC – RAS,. The rainfall distribution was tested using the Log Normal, Pearson Log Type III, and Gumbel methods, and tested for compatibility with the chi-square test. The results showed that the distribution of Pearson Log Type III was most consistent with the data (kurtosis statistical value γk = 3.247). The planned rainfall for T = 2 years is 165.7 mm, and T = 100 years is 329.3 mm (Normal Log), which is used to calculate the rainfall intensity (Talbot, Ishiguro, Sherman method) and the planned flood discharge by the Rational method (Q = 0.278· C·Cs· I·A). The planned flood discharge obtained is 9,399 m³/s, greater than the existing channel capacity of 8,053 m³/s, so channel replanning is required. Hydraulic simulations using HEC – RAS 5.1 showed that the proposed drainage design (30 cm × 40 cm cover box) was able to accommodate the design rainfall (25-year re-period) without overflow. The study contributes to residential flood mitigation through the calculation of adequate plan discharge and drainage design recommendations, as well as the use of hydrodynamic models to ensure the performance of the channel to the standard.